Efficacy and safety of immune checkpoint inhibitors combined with chemotherapy in patients with extensive-stage small cell lung cancer: a systematic review and meta-analysis of randomized controlled trials - Chen, Chunlan; Tian, Peng; Zhong, Jiangshan; Fan, Xianming (Frontiers in Oncology, 2023)
Objective Many clinical trials of immune checkpoint inhibitors (ICIs) in combination with chemotherapy in the first-line treatment of extensive-stage small cell lung cancer (ES-SCLC) have been initiated, but the conclusions of these trials are not identical. This meta-analysis aimed to comprehensively collect these randomized clinical controlled trials (RCTs) to evaluate the efficacy and safety of ICIs combined with chemotherapy in the first-line treatment of ES-SCLC. Methods We systematically searched PubMed, Embase, and ClinicalTrials databases, to find relevant studies published until October 2022.RevMan 5.4 software was used for statistical analysis. The Cochrane Risk of Bias Tool was adopted to evaluate the risk of bias in the included studies. The primary outcome of this study was overall survival (OS), while the secondary outcomes were progression-free survival (PFS), objective response rate (ORR), all grand AEs (AEs), and ≥ 3 grand adverse events (≥ 3 AEs). Results A total of 780 articles were obtained in the initial examination, which was screened by layer and finally included 8 studies including 3367 patients. Six studies evaluated the efficacy of PD-1/PD-L1 inhibitors (Pembrolizumab, Nivolumab, Atezolizumab, Durvalumab, Adebrelimab, Serpulimab) combined with chemotherapy, and two studies evaluated the efficacy of CTLA-4 inhibitors (Ipilimumab) in combination with chemotherapy. The results showed that compared to chemotherapy alone, ICIs combined with chemotherapy significantly improved patients’ OS (HR=0.8, 95% CI (0.72-0.85), P<0.05), PFS (HR = 0.72, 95% CI (0.63-0.83), P < 0.05), and ORR(RR=1.08, 95% CI: 1.03-1.13, P<0.05), but patients would experience more any grand AEs and ≥3 grand AEs. Subgroup analysis showed that the PD-1/PD-L1 group performed better than the CTLA-4 group in both efficacy and safety. And ICIs plus chemotherapy significantly improved OS and PFS in patients regardless of age, gender, and performance status. Conclusion The addition of ICIs to chemotherapy resulted in significant improvements in both PFS and OS for patients with ES-SCLC, but patients would experience more AEs.